Month of the Year and Pre- Holiday Effects In Indonesia and Malaysia Shari’ah Compliance - Malini, Helma; Jais, Mohammad (UI Scholars Hub, 2014)
This paper investigates the existence of two anomalies in Indonesia and Malaysia Shari’ah compliance; the month of the year and pre-holiday effect, and their implication for stock market efficiency. Investing in Shari’ah compliant is different from investing in conventional stock. Conventional stock market followed the capital market set of rules and law, while Shari’ah follows not only followed the capital market set of laws but also the Islamic principles. Most of the previous studies investigated issues related to the conventional stock market, this study take one step further by investigating issue related to Shari’ah compliant instrument and make comparison between both Shari’ah compliance stock market in Indonesia and Malaysia. We document high and significant returns in month and pre-holiday in Indonesia and Malaysia stock market that represent by the Shari’ah compliance. Our result indicate that the month of the year effect is prevalent in Indonesia and Malaysia Shari’ah compliance.